Role of PTHrP(1‐34) Pulse Frequency Versus Pulse Duration to Enhance Mesenchymal Stromal Cell Chondrogenesis. Issue 12 (21st March 2016) - Fischer, Jennifer; Ortel, Marlen; Hagmann, Sebastien; Hoeflich, Andreas; Richter, Wiltrud
Abstract : Generation of phenotypically stable, articular chondrocytes from mesenchymal stromal cells (MSCs) is still an unaccomplished task, with formation of abundant, hyaline extracellular matrix, and avoidance of hypertrophy being prime challenges. We recently demonstrated that parathyroid hormone‐related protein (PTHrP) is a promising factor to direct chondrogenesis of MSCs towards an articular phenotype, since intermittent PTHrP application stimulated cartilage matrix production and reduced undesired hypertrophy. We here investigated the role of frequency, pulse duration, total exposure time, and underlying mechanisms in order to unlock the full potential of PTHrP actions. Human MSC subjected to in vitro chondrogenesis for six weeks were exposed to 2.5 nM PTHrP(1‐34) pulses from days 7 to 42. Application frequency was increased from three times weekly (3 × 6 h/week) to daily maintaining either the duration of individual pulses (6 h/day) or total exposure time (18 h/week; 2.6 h/day). Daily PTHrP treatment significantly increased extracellular matrix deposition regardless of pulse duration and suppressed alkaline‐phosphatase activity by 87%. High total exposure time significantly reduced cell proliferation at day 14. Pulse duration was critically important to significantly reduce IHH expression, but irrelevant for PTHrP‐induced suppression of the hypertrophic markers MEF2C and IBSP . COL10A1, RUNX2, and MMP13 expression remained unaltered. Decreased IGFBP‐2, ‐3, and ‐6 expression suggested modulated IGF‐I availability in PTHrP groups, while drop of SOX9 protein levels during the PTHrP‐pulse may delay chondroblast formation and hypertrophy. Overall, the significantly optimized timing of PTHrP‐pulses demonstrated a vast potential to enhance chondrogenesis of MSC and suppress hypertrophy possibly via superior balancing of IGF‐ and SOX9‐related mechanisms. J. Cell. Physiol. 231: 2673–2681, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Daily PTHrP treatment significantly increased extracellular matrix deposition regardless of pulse duration and suppressed alkaline‐phosphatase activity by 87%. Pulse duration was critically important to significantly reduce IHH expression, but irrelevant for PTHrP‐induced suppression of the hypertrophic markers MEF2C and IBSP. Decreased IGFBP‐2 and ‐6 expression suggested modulated IGF‐I availability in PTHrP groups while drop of SOX9 protein levels during the PTHrP‐pulse may delay chondroblast formation and hypertrophy. Overall, the significantly optimized timing of PTHrP‐pulses demonstrated a vast potential to enhance chondrogenesis of MSC and suppress hypertrophy possibly via superior balancing of IGF‐ and SOX9‐related mechanisms.